2010
DOI: 10.1088/0004-637x/725/2/2059
|View full text |Cite
|
Sign up to set email alerts
|

The Three-Dimensional Structure of Interior Ejecta in Cassiopeia a at High Spectral Resolution

Abstract: We used the Spitzer Space Telescope's Infrared Spectrograph to create a high-resolution spectral map of the central region of the Cassiopeia A (Cas A) supernova remnant, allowing us to make a Doppler reconstruction of its threedimensional structure. The ejecta responsible for this emission have not yet encountered the remnant's reverse shock or the circumstellar medium, making it an ideal laboratory for exploring the dynamics of the supernova explosion itself. We observe that the O, Si, and S ejecta can form b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
75
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 49 publications
(101 reference statements)
12
75
0
Order By: Relevance
“…The high spectral resolution Spitzer mapping shows that the sheets are composed of thin filaments (1. 5 or 0.03 pc thick) with several filaments along any given line-ofsight (Isensee et al 2010). Therefore, we estimate the combined thickness of the front and back sheets to be of order 10 which translates to L = 0.16 pc at the distance to Cas A of 3.4 kpc Reed et al 1995).…”
Section: Geometry Of Cas Amentioning
confidence: 92%
See 1 more Smart Citation
“…The high spectral resolution Spitzer mapping shows that the sheets are composed of thin filaments (1. 5 or 0.03 pc thick) with several filaments along any given line-ofsight (Isensee et al 2010). Therefore, we estimate the combined thickness of the front and back sheets to be of order 10 which translates to L = 0.16 pc at the distance to Cas A of 3.4 kpc Reed et al 1995).…”
Section: Geometry Of Cas Amentioning
confidence: 92%
“…DeLaney et al (2010) and Isensee et al (2010) showed that the unshocked ejecta, as traced by [O iv] and [Si ii] emission, are concentrated onto two thick sheets interior to the reverse shock-one front and one rear. The two sheets are separated by a much lower density region, where only a little emission is seen.…”
Section: Geometry Of Cas Amentioning
confidence: 99%
“…Such emission has not yet been observed (Isensee et al 2010;DeLaney et al 2014), implying either that the interior iron ejecta are so diffuse that they cannot be detected, or that they are in a higher ionization state due to photoionization from soft X-rays from the ejecta and thus cannot be observed by Spitzer, or that the ejecta are not present. Deeper observations to probe for a cold, diffuse source of iron are required to further constrain the Fe/Ti ratio in the interior of the remnant.…”
Section: The Unshocked Interiormentioning
confidence: 99%
“…For the shocked ejecta, we can use the [Ar II] 6.99 μm 3D maps from Spitzer Isensee et al 2010). Seen in the plane of the sky, the ejecta forms the feature known as the "bright ring," while in 3D there are circular structures in the plane of the sky (labeled as the "north ring" and the "NE jet" structures, Figure 10).…”
Section: Ti Ejecta and Infrared/optical Featuresmentioning
confidence: 99%
“…In particular, it might allow one to discriminate our gravitational tug-boat mechanism from scenarios like the neutrino-driven kicks discussed by Fryer & Kusenko (2006), who expect the stronger explosion (and thus enhanced explosive nucleosynthesis) in the direction of the NS motion. High-resolution spectral investigations of young SN remnants like Puppis A (Katsuda et al 2008(Katsuda et al , 2010, G11.2-0.3 (Moon et al 2009), and Cassiopeia A (Isensee et al 2010;DeLaney et al 2010;Rest et al 2011;Hwang & Laming 2012) in different wavebands may offer a promising perspective.…”
Section: Introductionmentioning
confidence: 99%